Recent progress in understanding, diagnosing, and treating hepatocellular carcinoma - Maluccio, Mary; Covey, Anne (CA: a cancer journal for clinicians, 2012)
Hepatocellular carcinoma (HCC) is one of the few cancers in which a continued increase in incidence has been observed over several years. As such, there has been a focus on safe and accurate diagnosis and the development of treatment algorithms that take into consideration the unique complexities of this patient population. In the past decade, there have been improvements in nonsurgical treatment platforms and better standardization with respect to the diagnosis and patient eligibility for liver transplant. How to navigate patients through the challenges of treatment is difficult and depends on several factors: 1) patient‐related variables such as comorbid conditions that influence treatment eligibility; 2) liver‐related variables such as Child‐Pugh score; and 3) tumor‐related variables such as size, number, pattern of spread within the liver, and vascular involvement. The objectives of this review are to put into perspective the current treatment options for patients with HCC, the unique advantages and disadvantages of each treatment approach, and the evidence that supports the introduction of sorafenib into the multidisciplinary management of HCC. CA Cancer J Clin 2012;. © 2012 American Cancer Society.